¿Nueva vida para Unión Pro Paz? - Anich Sfeir, Gabriel (Revista Tribuna Internacional, 2023)
The United Nations’ “Uniting for Peace” resolution is a mechanism that enables the General Assembly to discuss issues vetoed by the Security Council. This resolution was constantly employed during the Cold War and, after decades of disuse, it was reactivated in 2022 against the Russian veto on the invasion of Ukraine. The Assembly has recommended various measures for Uniting for Peace in the exercise of its powers under the Charter of the United Nations. While the Assembly cannot adopt binding measures or authorize the use of force, Uniting for Peace is a relevant political tool in the maintenance of peace and security in the 21st century as well as in offering possibilities for the control and accountability of the Security Council and the use of veto power by permanent members.